Bioprospecting of Bacillus pumilus as biocontrol against fungal plant pathogens - Ade Fajrian; Rejeki Siti Ferniah; Anto Budiharjo (Jurnal Biologi Tropika, 2019)
The genus Bacillusis one of the wellknown group of bacteria as Plant Growth-Promoting Rhizobacteria (PGPR) that can support plant growth or otherwise control the plant pathogens. In this study, three strain of B. pumilusfrom BIOTEC culture collection (BCC 7507, TBRC 2887 and TBRC 2903) were investigated for their potential to be used as fungal pathogen control.  The growth characteristics of these B. pumilusstrains were determined by making the growth curve of each strain. Further, antagonistic activity of B. pumilusagainst the anthracnose pathogens C. capsici, C. gloeosporioidesand C. acutatum, the rice dirty panicle pathogen Curvularia lunata, the leaf spot pathogen Alternaria brassicicola, and the rice blast pathogen Magnoporthe griseawere evaluated by identified the inhibition zone from their activity. Then, the secondary metabolites produced by these Bacillusstrains were also examined using anti-fungal activity assays. All B. pumilusstrains showed very low biocontrol activity against M. grisea, but not against C. acutatum, C. Capsici, C. gloeosporioides, A. brassicicolaand C. lunata. Culture extracts derived from these strains did not show any activity against M. griseain the spore germination inhibition assay.  These results showed that the three B. pumilusstrains did not exhibit strong potential for application as biocontrol agent.